Bone Sarcomas: From Biology to Targeted Therapies. (27th November 2012) - Gaspar, Nathalie; Di Giannatale, Angela; Geoerger, Birgit; Redini, Françoise; Corradini, Nadège; Enz-Werle, Natacha; Tirode, Franck; Marec-Berard, Perrine; Gentet, Jean-Claude; Laurence, Valérie; Piperno-Neumann, Sophie; Oberlin, Odile; et al.
Abstract : Primary malignant bone tumours, osteosarcomas, and Ewing sarcomas are rare diseases which occur mainly in adolescents and young adults. With the current therapies, some patients remain very difficult to treat, such as tumour with poor histological response to preoperative CT (or large initial tumour volume for Ewing sarcomas not operated), patients with multiple metastases at or those who relapsed. In order to develop new therapies against these rare tumours, we need to unveil the key driving factors and molecular abnormalities behind the malignant characteristics and to broaden our understanding of the phenomena sustaining the metastatic phenotype and treatment resistance in these tumours. In this paper, starting with the biology of these tumours, we will discuss potential therapeutic targets aimed at increasing local tumour control, limiting metastatic spread, and finally improving patient survival.